Steadfastness and Da-sein. The Thinking of Ereignis and Transcendental Philosophy - Gómez Algarra, César (2022)
This paper attempts to trace and identify Heidegger’s attacks against transcendental philosophy, as they appear in his posthumous texts of the 1930sand 1940s, that is, the so-called treatises on Ereignis, and in the last volumes of the Gesamtausgabe. I will focus especially on volume 82, published in 2018, which includes a series of Heidegger’s annotations and re-readings concerning his own published work —this volume has not drawn a lot of attention in recent research. This way of proceeding will allow to show the author’s own critiques of his treatise Being and Time, and why he questions it a posteriori as a work of transcendental philosophy. After presenting the critique against all transcendental philosophy and transcendental subjects, it will be possible to describe the other possibility found in these posthumous works: the idea of steadfastness or “standing within” (Inständigkeit) in Being. Finally I will point out some difficulties and limitations implicit within the will to overcome our modern philosophical tradition, as it is shown by the project of a history of Be-ing (Geschichte des Seyns) as another beginning (andere Anfang) of thinking.